Grave reservations : a novel [large type] - Priest, Cherie (Priest, Cherie, Booking agents, 2023)
"A psychic travel agent and a Seattle PD detective solve a murder in this quirky mystery in the vein of Lisa Lutz's The Spellman Files and Charlaine Harris's Aurora Teagarden series. Meet Leda Foley: devoted friend, struggling travel agent, and inconsistent psychic. When Leda, sole proprietor of Foley's Flights of Fancy, impulsively re-books Seattle PD detective Grady Merritt's flight, her life changes in ways she couldn't have predicted. After watching his original plane blow up from the safety of the airport, Grady realizes that Leda's special abilities could help him with a cold case he just can't crack. Despite her scattershot premonitions, she agrees for a secret reason: her fiancé's murder remains unsolved. Leda's psychic abilities couldn't help the case several years before, but she's been honing her skills and drawing a crowd at her favorite bar's open-mic nights, where she performs Klairvoyant Karaoke--singing whatever song comes to mind when she holds people's personal effects. Now joined by a rag-tag group of bar patrons and pals alike, Leda and Grady set out to catch a killer--and learn how the two cases that haunt them have more in common than they ever suspected" --